2017
DOI: 10.1016/j.jss.2017.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Obscured by the cloud: A resource allocation framework to model cloud outage events

Abstract: As Small Medium Enterprises (SMEs) adopt Cloud technologies to provide high value customer offerings, uptime is considered important. Cloud outages represent a challenge to SMEs and micro teams to maintain a services platform. If a Cloud platform suffers from downtime this can have a negative effect on business revenue. Additionally, outages can divert resources from product development/delivery tasks to reactive remediation. These challenges are immediate for SMEs or micro teams with a small levels of resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The model has been proposed by Dunne and Malone [14], who analysed 300+ cloud outage events recorded for an enterprise cloud system (not better identified, but belonging to a small/medium enterprise) over an eighteen-month period. They tested seven models (Pareto, loglogistic, lognormal, gamma, exponential, logistic, and Weibull) through the Anderson-Darling test.…”
Section: The Pareto-lognormal Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The model has been proposed by Dunne and Malone [14], who analysed 300+ cloud outage events recorded for an enterprise cloud system (not better identified, but belonging to a small/medium enterprise) over an eighteen-month period. They tested seven models (Pareto, loglogistic, lognormal, gamma, exponential, logistic, and Weibull) through the Anderson-Darling test.…”
Section: The Pareto-lognormal Modelmentioning
confidence: 99%
“…In that paper, the correct premium has been computed for the case where the outage phenomenon is described by a Poisson process for occurrence of outages and by the generalized Pareto distribution for their duration. However, an alternative model has been recently introduced in the literature, based on an extensive measurement campaign on a private cloud [14] belonging to a small/medium company. In that paper, the interarrival time between successive outages is modelled through a Pareto distribution, while the duration of an outage is modelled by a lognormal distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ending time of the outage may be also reported wrongly, since most users do not take on themselves to report it, and we have to rely on the cloud provider announcing that the problem has been solved and the cloud is back to its fully operational state. Statistics of working periods and outages have been modelled in [19] with data coming from a small private cloud. Active measurement systems based on ICMP probing packets have been investigated in [20]- [22].…”
Section: Introductionmentioning
confidence: 99%
“…Exponential-exponential model (or Poisson-exponential), employed inMastroeni and Naldi (2011); • Exponential-Pareto (or Poisson-Pareto) that was proposed by Mastroeni et al (2019); Mastroeni and Naldi (2011) based on a dataset of customer-reported outages for five major cloud providers (Google, Amazon, Rackspace, Salesforce, Windows Azure); • Pareto-LogNormal model, proposed byDunne and Malone (2017) to describe the results of a measurement campaign in a small company running its own cloud.…”
mentioning
confidence: 99%